Hand Foot and Mouth Disease (HFMD) Educational Workshop for Preschool Teachers: An Interventional Study - Nurul Azmawati Mohamed @ Abd Aziz; Habibah Faroque; Mohd Dzulkhairi Mohd Rani; Nur Syazana Umar; Tengku Zetty Maztura Tengku Jamaluddin; Che Ilina Che Isahak; Siti Mariah Mahmud (JK Welfare & Pharmascope Foundation, 2024)
Hand, foot and mouth disease (HFMD) mainly affects children below ive years of age. The disease can be prevented by focusing on hand hygiene, disinfection of premises, and cough etiquette. Teachers at pre-school play a vital role in inculcating good hygiene habits among children. This project aimed to determine pre and post-intervention level of knowledge, attitude and practices on HFMD among pre-schools teachers. This study involved pre-school teachers from Ampang, Selangor, Malaysia who were invited to a 5-hour event ”HFMD: Infection Control Workshop”. Questionnaires on knowledge, attitude and practice on HFMD were distributed before and immediately after the event. A total of 112 teachers were recruited. All were female, mostly (90%) from government pre-schools with the mean age of 35.8. Post-intervention total means a score of knowledge increased significantly, notably on the causative agent (23%) and complications of HFMD (26-45%). Mean attitude scores were also significantly increased, especially regarding the cleaning of toys and sharing of utensils. Meanwhile, practice scores were very high during pre-intervention but were insignificantly reduced post-intervention. The intervention improved respondents’ knowledge and attitude significantly. Findings from this study highlighted the need to provide more HFMD program focusing on the basic information of the disease, including mode of transmission and clinical manifestation. We hope that the knowledge gained will be imparted to fellow teachers and children under their care towards minimising the spread of HFMD.